A systematic review and meta-analysis of animal models of binge eating - Part 1: Definitions and food/drink intake outcomes. (January 2022) - Rehn, Simone; Raymond, Joel S.; Boakes, Robert A.; Leenaars, Cathalijn H.C.
Highlights: Many publications fail to report operational definitions of bingeing in animals. Face validity is limited in some models that report binge-like intakes. Binge-like intakes are reliably observed across many animal models. Binge effect sizes vary with animal species, strain, and sex. Abstract: Binge eating involves consuming excessive amounts of food within a discrete period of time and is associated with significant impairments in binge-eating disorder and bulimia nervosa. While research on clinical binge eating has provided valuable aetiological insights, animal models allow for closer examination of environmental, biological, and developmental risk factors. Numerous animal models of binge eating exist and differ widely in operational definitions of bingeing, animal characteristics and methodological parameters. The current review aimed to synthesise the available published evidence on these models. A systematic review of binge definitions in 170 articles found most studies displayed good face validity. Meta-analyses on 150 articles confirmed that the amount of food or drink consumed by animals under binge conditions was larger than that of non-binge conditions across many protocols. The meta-regression revealed species, strain, and sex moderated binge effect size, with the largest effect observed in studies with female animals and mice. Risk of bias assessment identified that improved reporting of allocation, baseline characteristics and outcome assessment is required in future studies.